2019
DOI: 10.1038/s41598-019-54579-z
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of vitamin D-binding protein is associated with changes in insulin production in pancreatic beta-cells exposed to p,p′-DDT and p,p′-DDE

Abstract: Persistent organochlorine pollutants (POPs) gradually accumulate in the human organism due to their presence in the environment. Some studies have described a correlation between the level of POPs in the human body and the incidence of diabetes, but we know little about the direct effect of POPs on pancreatic beta-cells. We exposed pancreatic beta-cells INS1E to non-lethal concentrations of p,p′-DDT (1,1′-(2,2,2-Trichloroethane-1,1-diyl)bis(4-chlorobenzene)) and p,p′-DDE (1,1′-(2,2-dichloroethene-1,1-diyl)bis(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 63 publications
0
16
1
Order By: Relevance
“…DDE is a metabolite of the persistent endocrine disruptor DDT. Previous experiments performed in INS-1E cells showed that exposure to non-lethal concentrations of DDT or DDE changed insulin secretion and content/expression [58,68]. Upon 48 h treatment, low concentrations of DDT (1 fM to 1 μM) decreased GSIS in a non-monotonic manner, while all doses tested diminished intracellular insulin content [68].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…DDE is a metabolite of the persistent endocrine disruptor DDT. Previous experiments performed in INS-1E cells showed that exposure to non-lethal concentrations of DDT or DDE changed insulin secretion and content/expression [58,68]. Upon 48 h treatment, low concentrations of DDT (1 fM to 1 μM) decreased GSIS in a non-monotonic manner, while all doses tested diminished intracellular insulin content [68].…”
Section: Discussionmentioning
confidence: 97%
“…Upon 48 h treatment, low concentrations of DDT (1 fM to 1 μM) decreased GSIS in a non-monotonic manner, while all doses tested diminished intracellular insulin content [68]. In addition, INS-1E cells exposed for 1 month to a non-lethal concentration (10 μM) of DDT or DDE had lower mRNA levels of Ins1 and Ins2 as well as reduced expression of proinsulin and insulin [58]. On the other hand, DDE exposure increased insulin secretion in β-TC-6 cells [69], which agrees with our results that suggest an increase of GSIS at 10 nM and 1 μM DDE (insulin content remained unchanged in all concentrations tested).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we used 2-D electrophoresis coupled to mass spectrometry to find proteins possibly involved in mechanisms mediating a prolonged (1 month) effect of non-lethal concentrations of organochlorine pollutant p , p ‘-DDT in pancreatic beta-cells [ 6 , 21 ]. In our present study, we aimed to find proteins that change expression in NES2Y human pancreatic beta-cells when exposed to a high concentration of p , p ‘-DDT) and could be detected by 2-D electrophoresis.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we used 2-D electrophoresis coupled to mass spectrometry to find proteins possibly involved in mechanisms mediating prolonged (1 month) effect of non-lethal doses of organochlorine pollutant p,p ’-DDT in pancreatic beta-cells (6, 18). In our present study, we aimed to find markers of acute toxicity of lethal doses of p,p ’-DDT in human pancreatic beta-cells NES2Y, also employing 2-D electrophoresis.…”
Section: Introductionmentioning
confidence: 99%